Development of Learning Media Based on Smart Apps Creator to Improve Student’s Critical Thinking Skills - Rohman, Allif Silfiyana; Sugianto, Sugianto; Nurbaiti, Upik (Universitas Negeri Semarang, 2024)
Students have difficulty understanding abstract physics concepts because they are difficult to visualize. Based on the results of observations, students’ critical thinking skills are not yet improved and the learning process is still conventional. The use of learning media based on Smart Apps Creator by integrating the PBL learning model aims to improve student’s critical thinking skills. Based on the developing of ADDIE model, this study is development research or Research and Development (RD). During the 2022–2023 academic year, class XI–3 students at SMA Negeri 1 Kembang were the subjects of this study. The validation results by material experts were 88.75% and media experts were 89.38% in the very feasible category. Learning media based on Smart Apps Creator (SAC) is effective to improve student’s critical thinking skills as shown by the higher percentage of N-Gain test results for the experimental class, namely 76.82% with effective criteria, compared to the control class of 56.46% with quite effective criteria. Analysis of the profile student’s critical thinking skills after the action was shown by observation results of 84.52%. This shows that students in this class can improve their critical thinking skills.